The effect of a simulated soccer match on anterior cruciate ligament injury risk factors - Wright, M.; Chesterton, P.; Wijnbergen, M.; O`Rourke, A.; Macpherson, T. (International Journal of Sports Medicine, 2017)
To investigate the effect of within match fatigue on knee kinematics and jump kinetics in girls` soccer players, a quasi-experiment time series design was employed collecting data before, after and at 15-min intervals during a 90-min simulated soccer match. 15 girl players (age 13.1±1.4 years) performed a counter movement jump and a single-leg drop jump. Mean concentric force and flight time to contraction time ratio were derived from the counter movement jump. Knee valgus and flexion angles were calculated during the single-leg drop from 3-dimensional motion capture. Subjective ratings of perceived exertion (RPE) and readiness were collected at each time series. Small to large increases in RPE and reductions in readiness were observed throughout the match from baseline. Moderate to large improvements in mean concentric force were shown at 15, 75 and 90-min when compared to baseline. Flight time to contraction time ratio increased moderately at 15?min. Changes in kinematics were typically trivial or unclear however, small increases in knee valgus were shown after 30 min compared to baseline. Subjective measures may provide useful information to understand the physical response of young players to match play.